Spatial stimulus-response compatibility and affordance effects are not ruled by the same mechanisms - Ambrosecchia, Marianna; Marino, Barbara F. M.; Gawryszewski, Luiz G.; Riggio, Lucia (Frontiers in Human Neuroscience, 2015)
Stimulus position is coded even if it is task-irrelevant, leading to faster response times when the stimulus and the response locations are compatible (spatial Stimulus-Response Compatibility – spatial SRC). Faster responses are also found when the handle of a visual object and the response hand are located on the same side; this is known as Affordance Effect (AE). Two contrasting accounts for AE have been classically proposed. One is focused on the recruitment of appropriate grasping actions on the object handle, and the other on the asymmetry in the object shape, which in turn would cause a handle-hand Correspondence effect (CE). In order to disentangle these two accounts, we investigated the possible transfer of practice in a spatial SRC task executed with a S-R incompatible mapping to a subsequent affordance task in which objects with either their intact handle or a broken one were used. The idea was that using objects with broken handles should prevent the recruitment of motor information relative to object grasping, whereas practice transfer should prevent object asymmetry in driving handle-hand CE. A total of three experiments were carried out. In Experiment 1 participants underwent an affordance task in which common graspable objects with their intact or broken handle were used. In Experiments 2 and 3, the affordance task was preceded by a spatial SRC task in which an incompatible S-R mapping was used. Inter-task delays of 5 or 30 minutes were employed to assess the duration of transfer effect. In Experiment 2 objects with their intact handle were presented, whereas in Experiment 3 the same objects had their handle broken. Although objects with intact and broken handles elicited a handle-hand CE in Experiment 1, practice transfer from an incompatible spatial SRC to the affordance task was found in Experiment 3 (broken-handle objects), but not in Experiment 2 (intact-handle objects). Overall, this pattern of results indicate that both object asymmetry and the